Separation and identification of some derivatised diterpenes and triterpenes in Rosemary (Rosmarinus officinalis L.) by gas chromatography and mass spectrometry - Islamčević-Razboršek, Maša; Vončina, Ernest; Doleček, Valter; Brodnjak-Vončina, Darinka (Univerzita Pardubice, 2006)
A rapid analytic method for isolation, separation and determination of some phenolic diterpenes and triterpenes from fresh and dry rosemary leaves (Rosmarinus officinalis L.) has been developed. The components identified in the plant extract were trimethylsilylated derivatives of rosmarinic acid, phenolic diterpenes, carnosol and carnosic acid, pentacyclic triterpenoids, ursolic, oleanolic, betulinic acid and betulin. Experiments were performed to establish the optimum conditions for solvent selection, mode and duration of extraction, derivatisation, and to set chromatographic conditions, as well. The enumerated compounds have numerous similarities in the chemical and pharmacological character. Publications dealing with separation and determination of diterpenes and triterpenes in plant material report many different analytic methods, but most extended are high performance liquid chromatography and thin layer chromatography. The procedures are complicated, since the separation and the determination of terpenic compounds are difficult because of structure similarity. Therefore, gas chromatography and mass spectrometry were used as methods enabling good separation and parallel determination of phenolic diterpenes and triterpenes.
Keywords: rozmarýn lékařský; stanovení účinných látek; terpeny; deriváty; plynová chromatografie; Hmotnostní spektrometrie